Prospective Validation of a Screening Biomarker Approach Combining Amino-Terminal Pro-Brain Natriuretic Peptide With Galectin-3 Predicts Death and Cardiovascular Events in Asymptomatic Hemodialysis Patients. (May 2018) - Voroneanu, Luminita; Siriopol, Dimitrie; Apetrii, Mugurel; Hogas, Simona; Onofriescu, Mihai; Nistor, Ionut; Kanbay, Mehmet; Dumea, Raluca; Cusai, Silvia; Cianga, Petru; Constantinescu, Daniela; Covic, Adrian
Cardiovascular (CV) disease is a major cause of death in hemodialysis patients. Biomarkers used to identify high-risk asymptomatic patients would allow early evaluation of cardiac dysfunction and appropriate therapeutic intervention. Amino-terminal pro-brain natriuretic peptide (NT-proBNP) and galectin-3 (Gal-3) may serve this purpose. Plasma levels of NT-proBNP and Gal-3 were measured in 173 patients. Patients were prospectively followed for occurrences of major CV events or death. The association of NT-proBNP and Gal-3 with outcome was analyzed. The prognostic abilities for the combined outcome of Gal-3 and/or NT-proBNP were evaluated. During a median follow-up of 36 months, there were 47 incident outcomes (death and CV events). In the univariable Cox analysis, age, hypertension, albumin, phosphorus levels, and combined elevation of NT-proBNP with Gal-3 above the median (hazard ratio [HR] = 3.65, 95% confidence interval [CI] = 1.45-9.21) were associated with outcomes. In multivariable Cox analysis, both NT-proBNP and Gal-3 values above the median remained associated with outcomes (HR = 3.34, 95% CI = 1.30-8.56). In clinically asymptomatic dialysis patients, combined use of NT-proBNP and Gal-3 may improve risk stratification for death and CV events.